KONTEKS SYUKUR SEBAGAI PARADIGMA DALAM PERSPEKTIF PENDIDIKAN ISLAM - Moh. Fuadi (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2018)
Education is a rehumanisme, that was oriented to form individuals who able to understand the reality it self and the surrounding communities. The aim of education is to create significant social change in the life of mankind. One of the contents of the national education goals is to appreciate the reality of humanity and the potential that owned learners (human). Islam in its victorius was a center of the study of various discipline. It was proved by the emergence of Muslim scientists. But over time, the Islamic intellectualism began to decline along with cultural understanding and taqlid, whereas al-Qur`an have many signaled to examines all disciplines, not limited to the religious sciences. It can be seen from the verses of al-Qur`an that ordered to examine the verses kauniyah. Thus Islamic comprehensive assessment is a paradigm of Humanist Islamic Education or in other words, humanize human accordance with the primary task of man as a khalifah on earth. Keywords: Islamic Education, Paradigm, and Humanist.